2012
DOI: 10.1002/poc.3068
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations of pyridine derivatives as potential high energy density materials

Abstract: Density function theory has been employed to study pyridine derivatives at the B3LYP/6-31 G(d,p) and B3P86/6-31 G(d,p) levels. The crystal structures were obtained by molecular mechanics methods. The heats of formation (HOFs) were predicted based on the isodesmic reactions. Detonation performance was evaluated by using the Kamlet-Jacobs equations based on the calculated densities and HOFs. The thermal stability of the title compounds was investigated by the bond dissociation energies and the energy gaps (ΔE LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Predicted densities and detonation properties of the title compounds compared with calculated values of other two polynitroimidazoles from references and experimental values of RDX, HMX and CL-20 [14] 1465.70 8.23 (8.13) [14] 29.83(28.10) [14] 4,5-DNI À30.37 91.61 1.75(1.72) [15] 1465.69 8. 10 28…”
Section: Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicted densities and detonation properties of the title compounds compared with calculated values of other two polynitroimidazoles from references and experimental values of RDX, HMX and CL-20 [14] 1465.70 8.23 (8.13) [14] 29.83(28.10) [14] 4,5-DNI À30.37 91.61 1.75(1.72) [15] 1465.69 8. 10 28…”
Section: Compmentioning
confidence: 99%
“…[4][5][6] Due to the high heat of formation (HOF), good thermal stability, low sensitivity and excellent detonation performance, nitroimidazoles have drawn renewed attention from explosive researchers currently. [7][8][9][10] The geometric, thermodynamic and detonation properties of 4(5)-nitroimidazole, 4,5-dinitroimidazole (4,5-DNI), 2,4-dinitroimidazole (2,4-DNI), amino-and methyl-substituted trinitrodiazoles and aminonitroimida-zoles have been already studied. [11][12][13][14] However, most of experimental and theoretical studies were concentrated on monocyclic nitrodiazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) [13,14] has emerged as a very reliable and economical tool to predict the chemical and physical properties of unknown energetic materials. The B3LYP/6-31G (d,p) basis set, which can not only produce reliable geometries and energies, but also require less time and computer resources, was used to compute the title compounds on a Gaussian 03 package [15].…”
Section: Methodsmentioning
confidence: 99%
“…16 The descriptors A, n, ands tot 2 were calculated by using the computational procedures proposed by Bulat et al 17 This approach has been demonstrated to be a reliable way in prediction the heats of sublimation of energetic materials. 18,19 The detonation velocity (D) and detonation pressure (P), which are two important parameters in evaluating the explosive properties of energetic materials, can be estimated by the empirical Kamlet-Jacobs equations: 20…”
Section: Methodsmentioning
confidence: 99%